Compromised osteogenic effect of exosomes internalized by senescent bone marrow stem cells via endocytoses involving clathrin, macropinocytosis and caveolae - Qi, Lei; Ge, Weiwen; Pan, Cancan; Jiang, Weidong; Lin, Dan; Zhang, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Stem cell senescence leads to progressive functional declines and disrupts the physiological homeostasis of bone environment. Stem cell-derived exosomes are emerging as promising therapeutical approaches to treat diverse aging-related osseous diseases. Herein, a previously reported osteoinductive exosome (OI-exo) was applied as a therapeutic agent for bone repair in aging individuals and its internalization mechanisms in senescent bone marrow stem cells (BMSCs) were explored. The results demonstrated that OI-exos derived from young BMSCs could partially rescue the proliferation, osteogenic differentiation and alleviate aging phenotypes in vitro. OI-exo-delivered hierarchical mesoporous bioactive glass (MBG) scaffold effectively promote in vivo bone formation in aging rat cranial defect model. However, the osteogenic effects of OI-exo both in vitro and in vivo were compromised in senescent individuals and for aging BMSCs compared to younger ones. This study revealed that non-senescent BMSCs internalized exosomes exclusively via clathrin-mediated endocytosis, while senescent BMSCs additionally evoked macropinocytosis and caveolae-mediated endocytosis to mediate the internalization of exosomes. The alteration of endocytic manner of senescent BMSCs and the involvement of macropinocytosis might be responsible for the compromised effects of therapeutical exosomes. The phenomena discovered in this study could also be extended to other scenarios where drugs or treatments exerted compromised effects in aging individuals. The influence of endocytic manner, avoidance of macropinocytosis-related negative effects should be taken into considerations in future therapeutic design for aging populations.